TANGERANG HOTEL ROOM RESERVATION SYSTEM USING VISUAL BASIC 6.0 - Wanda Kiranam; Cut Asiana Gemawaty, Skom, MMSI Cut Asiana Gemawaty, Skom, MMSI (Jurnal Sistem Informasi, 2006)
The rapid development of computers these days almost covers all areas of life one of them is the use of computers or computerized on hospitality. Development of Personal Computers that increasingly sophisticated and increasingly rapid process but with the form of an increasingly small compared with the initial findings so the price becomes more affordable and easier to understand.Part hospitality is very broad in scope that will be discussed here is only part of a reservation which consists of the Reservation, Information, Service Desk, Front Desk or Reception and cashier. However, in the Hotel Reservation Tangerang existing only, Reseption and cashier. Scientific Writing is aimed at designing systems for data processing and reservation about the guests staying and ciata-data associated with it. In acquiring data and information rnenggunakan library data collection methods and field study. In the section of Tangerang hotel reservation all the things like the Reservation, Reception and Kasr done by one person alone so it is still lot of mistakes - mistakes, and the service system receptionis Hotels Tangerang also still having problems. Given Tangerang hotel reservation system is expected absence of errors is more fatal will happen.